FREQUENCY OF MALIGNANT VENTRICULAR ARRHYTHMIA IN NON- ST ELEVATION MYOCARDIAL INFARCTION (NSTEMI) DURING HOSPITALIZATION - muhammad rehan khan; Syed Azhar Sherazi; Badshah Noor; Amjad Abrar (Gomal Journal of Medical Sciences, 2017)
Background: The incidence of Non- St Elevation Myocardial Infarction NSTEMI is increasing. With the limited coronary care facilities, acute life-threatening arrhythmias is of major interest to guide the decision on the intensity of care at the time of admission. The objective of the study was to determine the frequency, time and outcome of ventricular arrhythmias in patients with NSTEMI during their hospital stay. Material and Method: This descriptive cross-sectional study was done in Cardiac Care Unit (CCU) of District Headquarter Teaching Hospital, Dera Ismail Khan, Pakistan, from January 2, 2015 to October 10, 2015. Sample size was 450. Sampling technique was nonprobability, consecutive. Patients with NSTEMI admitted in CCU were included. Patients with STEMI were excluded from the study. After detailed history, clinical examination and baseline routine investigations, the patients were managed conservatively. Patients were monitored for malignant ventricular arrhythmia and ECG were done on routine basis to document VT/VF as long as patients remained in hospital. Collected data was analysed using SPSS version 10 software for descriptive analysis. Result: Out of 450 patients, there were 260 (58%) males and 190 (42%) females with age ranging from 40 to 90 years and mean age of 60.47±9.7 years. Frequency of malignant ventricular arrhythmias was 22(5%). Out of 22 patients, malignant VT/VF occurred within 48 hours after enrollment in 15(68% ), while 7 patients (32%) had VT/ VF after 48 hours. Thirteen (59%) patients died due to ventricular arrhythmia. Conclusions: Frequency of malignant ventricular arrhythmias and mortality among patients with NSTEMI was high especially in males, between 51 to 75 years. Malignant VT/VF commonly occurred within 48 hours after admission.